2008
DOI: 10.1016/j.juro.2007.11.038
|View full text |Cite
|
Sign up to set email alerts
|

PCA3: A Molecular Urine Assay for Predicting Prostate Biopsy Outcome

Abstract: PCA3 is independent of prostate volume, serum prostate specific antigen level and the number of prior biopsies. The quantitative PCA3 score correlated with the probability of positive biopsy. Logistic regression results suggest that the PCA3 score could be incorporated into a nomogram for improved prediction of biopsy outcome. The results of this study provide further evidence that PCA3 is a useful adjunct to current methods for prostate cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
237
1
25

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 391 publications
(284 citation statements)
references
References 18 publications
21
237
1
25
Order By: Relevance
“…40 Despite good performance, the uPM3 was withdrawn from the market after introduction of the APTIMA assay (Gen-Probe, San Diego, CA, USA; PROGENSA for European countries) which provides several advantages: (1) The ability to use whole urine and detection of lower concentrations of RNA in clinical samples (as opposed to urine sediments used in methods discussed above); (2) The target capture technology using magnetic particles is more quantitative and user friendly than the RNA extraction methods required for RT-PCR; (3) The APTIMA PCA3 assay can be completed in o6 h, and because of its robustness and reproducibility it can be implemented in the clinical laboratory. 41 Several large studies have confirmed the good performance of this assay, [42][43][44][45][46] and the clinical results have recently been reviewed. 47 The addition of PCA3 to the urologist's diagnostic tools will not result in a state of certainty but the diagnostic sensitivity, specificity and predictive value are incrementally improved by its inclusion.…”
Section: Prostate Cancer Antigenmentioning
confidence: 87%
“…40 Despite good performance, the uPM3 was withdrawn from the market after introduction of the APTIMA assay (Gen-Probe, San Diego, CA, USA; PROGENSA for European countries) which provides several advantages: (1) The ability to use whole urine and detection of lower concentrations of RNA in clinical samples (as opposed to urine sediments used in methods discussed above); (2) The target capture technology using magnetic particles is more quantitative and user friendly than the RNA extraction methods required for RT-PCR; (3) The APTIMA PCA3 assay can be completed in o6 h, and because of its robustness and reproducibility it can be implemented in the clinical laboratory. 41 Several large studies have confirmed the good performance of this assay, [42][43][44][45][46] and the clinical results have recently been reviewed. 47 The addition of PCA3 to the urologist's diagnostic tools will not result in a state of certainty but the diagnostic sensitivity, specificity and predictive value are incrementally improved by its inclusion.…”
Section: Prostate Cancer Antigenmentioning
confidence: 87%
“…However, 12 additional studies included matched results of PCA3 and the comparators but enrolled men with both initial and repeat biopsies or they did not report biopsy history. 10,11,[35][36][37][38][39][40][41][42][43][44] Most often, the results from these studies were not stratified by biopsy history.…”
Section: Clinical Validitymentioning
confidence: 99%
“…Fifteen studies [9][10][11]30,32,[34][35][36][37][38][39][40][41][42][43]46 reported AUC estimates for tPSA and PCA3 in the same population. Overall, 13 [9][10][11]30,32,34,35,37,38,[40][41][42]46 of the15 studies found that the AUC of PCA3 was higher than that of tPSA.…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…6 Elevations in PCA3 gene transcripts in post-digital rectal examination (DRE) urine have been shown to be associated with prostate cancer in patients undergoing initial and repeat prostate biopsy. 7 In men undergoing repeat biopsy, studies have suggested that PCA3 may be superior to both PSA 8 and free PSA 9 in predicting the presence of prostate cancer. Furthermore, inclusion of PCA3 improved predictive accuracy of a multivariable model that evaluated probability of having prostate cancer in men with elevated PSA, with or without prior biopsy in a recent study by Chun et al 10 Based on these findings, PCA3 was included in a multivariable nomogram designed to predict the presence of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%